EFFECT OF TAX PLANNING, EARNINGS GROWTH, ASSET MANAGEMENT, AND STICKY COSTS ON FIRM VALUE (STUDY ON PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2016 – 2019) - Suak, Meilivia; Sondakh, Jullie J.; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This study aims to determine and analyze the effect of tax planning, profit growth, asset management, and inherent costs on firm value (study on property and real estate companies listed on the Indonesian stock exchange in 2016 – 2019). This type of research is quantitative research. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange as many as 65 companies. The sampling technique used purposive sampling technique based on certain criteria so that there were 47 property and real estate companies that were used as research samples. The data in this study were processed using SPSS version 20.0. The results show that Tax planning (X1) has a value of t hit < t table (1.954 < 1.973) and a significance of P = 0.052 > = 0.05 then H01 is accepted, and Ha1 is rejected, meaning that partially tax planning has no effect on firm value (Y) . Earnings Growth (X2) has a value of t hit > t table (3.712 > 2.048) and a significance of P = 0.000 < = 0.05 then H02 is rejected, and Ha2 is accepted, meaning that earnings growth partially affects significant firm value (Y). Management Asset (X3) has a value of t hit < t table (1.007 < 1.973) and a significance of P = 0.315 > = 0.05 then H03 is accepted, and Ha3 is rejected meaning that partially management assets have no effect significant on firm value (Y). Sticky Cost (X4) has a value of t hit < t table (1.577 < 2.048) and a significance of P = 0.117 > = 0.05, H04 is accepted, and Ha4 is rejected, meaning that partially sticky cost has no effect significant on firm value (Y).